1994
DOI: 10.1136/adc.71.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular malformations and association with karyotypes in Turner's syndrome.

Abstract: The aim of the study was to establish the prevalence of cardiovascular malformations in females with Turner's syndrome and analyse possible associations with the various karyotypes. One hundred and seventy nine of 393 females who had Turner's syndrome diagnosed in Denmark were examined. Complete chromosome analysis was available in all cases. Clinical examination, electrocardiography, and echocardiography including Doppler were performed.The distribution of the various karyotypes was 45,X, 58%; mosaic monosomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
2
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(148 citation statements)
references
References 11 publications
13
128
2
5
Order By: Relevance
“…10 In sonographically evaluated studies, the prevalence ranged from 17 to 26%. 1,3,11,12 In this study we found at least one cardiovascular anomaly (CVA) in 29.9%. Since all patients with cytogenetically diagnosed UTS attended either our endocrinologic or cardiologic outpatient department, there may be a potential bias, inherent in most hospital-based studies.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…10 In sonographically evaluated studies, the prevalence ranged from 17 to 26%. 1,3,11,12 In this study we found at least one cardiovascular anomaly (CVA) in 29.9%. Since all patients with cytogenetically diagnosed UTS attended either our endocrinologic or cardiologic outpatient department, there may be a potential bias, inherent in most hospital-based studies.…”
Section: Discussionmentioning
confidence: 90%
“…This finding and the usually not excludable presence of mosaicism make planning of phenotype mapping studies difficult. 1,3,12,16,17 Zinn et al investigated 28 Xp-females (age range 1.3-41.5 years), mapping deletions by fluorescent in situ hybridization (FISH) for several phenotypic features; none of them had CVA. 17 The short stature homeobox gene (SHOX) is the first and best gene described to be involved in UTS phenotype features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How should a person with 5% (or less) 45,X cells and 95% 46,XX cells be considered, knowing that normally a karyotype is performed on Table 1 Detailed list of abnormalities associated with Turner syndrome with the tentative frequency of a specific abnormality given as a percentage. The table is compiled from different sources (8,55,178,296,305,307,321,350).…”
Section: Introductionmentioning
confidence: 99%
“…(27) In addition to valve morphology, more complete phenotypic classifications also include typing of aortic dilation. (25) In most patients, a BAV is an isolated anomaly, but can be more prevalent in certain conditions ( (47)(48)(49) 23% (50) 84 -89% (51,52) 39 -47% (53,54) 14 -30% (56)(57)(58) 5 -11% (55,59) Notes Large variability due in part due to heterogeneous reporting and nomenclature Subaortic stenosis predisposes to valve damage leading to aortic regurgitation Recurrence of subaortic stenosis after resection is common (20%) BAV was not initially described as part of the Shone complex Frequent structural abnormalities of aortic valve are present (55) 95% show R-L cusp fusion High prevalence of both ascending aortic dilation and aortic coarctation…”
Section: Phenotypementioning
confidence: 99%